2022
DOI: 10.3389/fenvs.2022.778544
|View full text |Cite
|
Sign up to set email alerts
|

Pollution level of trace metals (As, Pb, Cr and Cd) in the sediment of Rupsha River, Bangladesh: Assessment of ecological and human health risks

Abstract: The study area was selected in the Rupsha river basin and the sediment samples were collected to determine trace metal concentrations of As, Pb, Cd, and Cr along with biological effects, and potential ecological and human health hazards for adults and children. The concentrations of trace metals were detected from sixty composite sediment samples using an Atomic Absorption Spectrophotometer (AAS) following some sequential analytical procedures. The mean concentrations of trace metals were organized in the desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 107 publications
2
7
0
Order By: Relevance
“…However, the I geo value of Cr, As, Cu and Zn indicated uncontamination ( I geo < 0) state of the sediments of all the studied sites except for S1 and S2. The present finding is similar to the findings of Kubra et al [ 26 ] who reported the mean value of As and Cr was (0< I geo ) responsible for uncontamination and the mean value of Pb (winter) and Cd was ( I geo >0) responsible for moderately contamination of the Rupsha River. Consequently, Cd was responsible for the contamination of Mongla port area during wet season and major contributors for maximum Pb and Cd values might be atmospheric pollution, petroleum, municipal wastes, and discarded materials from the port region which supports the findings Chakraborty et al [ 25 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…However, the I geo value of Cr, As, Cu and Zn indicated uncontamination ( I geo < 0) state of the sediments of all the studied sites except for S1 and S2. The present finding is similar to the findings of Kubra et al [ 26 ] who reported the mean value of As and Cr was (0< I geo ) responsible for uncontamination and the mean value of Pb (winter) and Cd was ( I geo >0) responsible for moderately contamination of the Rupsha River. Consequently, Cd was responsible for the contamination of Mongla port area during wet season and major contributors for maximum Pb and Cd values might be atmospheric pollution, petroleum, municipal wastes, and discarded materials from the port region which supports the findings Chakraborty et al [ 25 ].…”
Section: Resultssupporting
confidence: 92%
“…5 ). The PLI values were akin to the findings of Kubra et al [ 26 ] in the Rupsha River. The mean PLI value during the present study was recorded as 0.659 which was much lower compared to the results of Chakraborty et al [ 25 ] as they recorded the mean PLI values of 1.26 and 1.97 during the rainy and dry season, respectively from the surface sediments of the Mongla port area, Bangladesh.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Rivers play a vital role in the water cycle and are one of the world's most important suppliers of freshwater and nutrients (Kubra et al 2022). In the river, flora and fauna can accumulate toxic metal(loid)s from different sources, which may end up after penetrating the human body through the food chain and create serious health disorders (Qiu 2015;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%